Intellectual Property Rights as Joint Property from a Comparative Legal Perspective in Indonesia, the United States, and Europe - Yudika Dwi Erwanda; Darmawan Darmawan; Azhari Azhari (International Forum of Researchers and Lecturers, 2026)
This study examines the regulation of copyright royalties as joint property in Indonesia, the United States, and Europe, aiming to provide recommendations for better legal implementation. The research employs a normative juridical method with a comparative legal approach, utilizing library research and qualitative analysis of primary and secondary legal materials. The findings indicate that Indonesia, the United States, and Europe share common ground in recognizing royalties derived from copyright as joint property when such economic benefits are obtained during marriage. However, significant differences exist in their approaches. European countries, particularly Spain and the Republic of Moldova, clearly distinguish between exclusive rights and economic rights, where copyright remains the creator's personal property while royalties are classified as joint property. The United States demonstrates considerable flexibility through state-level regulations, adopting either community property systems or equitable distribution systems. Indonesia, through Decision No. 1622/PDT.G/2023/PA.JB, has begun recognizing royalties as joint property. Nevertheless, Indonesia still requires clearer and more comprehensive regulations to ensure legal certainty regarding the status of royalties as joint property and their distribution following divorce. This study contributes to developing legal frameworks that balance protecting creators' personal rights with the principle of fairness in family law.